2021
DOI: 10.1007/s40121-021-00542-3
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime–Avibactam-Based Versus Tigecycline-Based Regimen for the Treatment of Carbapenem-Resistant Klebsiella pneumoniae-Induced Pneumonia in Critically Ill Patients

Abstract: Introduction:The aim of the present study was to assess the safety profile and outcomes of a ceftazidime-avibactam (CAZ-AVI)-based regimen and compare them with those of a tigecycline (TGC)-based regimen in intensive care unit (ICU) for the treatment of carbapenem-resistant Klebsiella pneumoniae (CRKP), which is classified into hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP). Methods: Clinical and microbiological cure rates, 28-day survival rates, and safety evaluation findings were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Several studies have demonstrated that CAZ-AVI is more effective against CRKP than polymyxins and tigecycline. 7–10 However, the risk factors associated with treatment failure of CAZ-AVI remain unclear. Additionally, previous in vitro studies have shown that CAZ-AVI, when combined with other agents, exhibits high synergistic activity against CRKP.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that CAZ-AVI is more effective against CRKP than polymyxins and tigecycline. 7–10 However, the risk factors associated with treatment failure of CAZ-AVI remain unclear. Additionally, previous in vitro studies have shown that CAZ-AVI, when combined with other agents, exhibits high synergistic activity against CRKP.…”
Section: Introductionmentioning
confidence: 99%
“… 56 In another study, ceftazidime–avibactam was a promising therapeutic option for the treatment of CRKP-induced pneumonia. 57 This variation in the susceptibility patterns may be attributed to the difference in the prescribed antibiotics from certain geographic areas to others and heterogeneity of CRKP strains side by side with the strain variability according to the clinical sites.…”
Section: Discussionmentioning
confidence: 99%
“…For the carbapenemase-producing Enterobacterales -related infections (including KPC- and OXA-48-producing strains), several retrospective studies have compared CZA with colistin [ 39 , 40 , 41 , 42 ] or tygecycline [ 43 ], showing a better clinical cure rate with CZA.…”
Section: What Is To Be Learnt From the Published Studies?mentioning
confidence: 99%